Desafíos y oportunidades que presenta la exportación de fresas en Colombia (2025)
This study aims to carry out an analysis of the commercialization of strawberries to international markets based on a bibliographic review of secondary sources and statistical data regarding imports and exports provided by the TradeMap database. In this study, the main markets in which Colombian strawberries are most competitive, the different tariff headings under which this type of product is marketed, its performance and market share are observed. Likewise, the main countries that import and export this type of product worldwide are shown. On the other hand, through a bibliographic review, the common denominators regarding the topics addressed by the research of various authors on this subject are shown in order to know the interests, needs and difficulties that the international marketing of this product presents. Finally, to establish the challenges and opportunities that the export of strawberries presents to Colombia, an aspect in which the study reflects relevant aspects on challenges related to the type of product, the companies that market them, the demands demanded by the international market for the export of these foods together with the preferences of consumers in these nations and their facilities to achieve efficient logistics taking into account the optimization of times and processes.